In-Utero effects of the crude ethanolic extract of the leaves of mitragyna speciosa on neural tube formation in rats - Muhammad, Bala Yauri; Abdullahi, Abubakar Danjuma; Abd Kadir, Siti Nur Sharida; Abdul Razak, Tariq; Ahmed, Qamar Uddin (Society of Applied Sciences, 2010)
The developmental effects of in-utero administration of the crude ethanolic extract of the leaves of itragyna speciosa (MS) on neural tube in fetal rats were investigated. Pregnant Sprague-Dawley rats were dosed orally once daily by gavage, with graded (500, 1000 and 1500 mg/kg) doses of the extract between the 8th and 13th day prenatally. The control group received corn oil used as vehicle for the extract. On the 18th day of gestation, mothers were sacrificed and embryos removed and stained under established procedures. The embryos were then analyzed for the presence of neural tube defects (NTD) through measurements of the extent of vertebral arch closure and brain size. Results indicate that the medium (C) and high (D) (1000 & 1500mg/kg) doses but not the low (B) (500mg/kg) dose in comparison with control (A) group, significantly (p10.001) produced a widening of the vertebral arch in the thoracic, lumber and cervical regions of the spinal cord. The brain transverse diameter was also significantly (p10.05) increased by the high dose only. These effects were seen in the absence of any significant differences in litter size and other gross physical abnormalities. This study indicates that the crude extract of the leaves of MS is capable of selective neurotoxicity and producing spina bifida like NTD as characterized by altered brain size and neural tube formation, a finding that may have an important implication in the dependence liability associated with its use.